To solve this system of equations, we can use the method of elimination.
1. Multiply the first equation by 4 and the second equation by -1 to eliminate x:
-4x + 24y = 52
-4x + 10y = 10
2. Now subtract the second equation from the first equation:
24y - 10y = 52 - 10
14y = 42
y = 3
3. Substitute y = 3 into the first equation:
-x + 6(3) = 13
-x + 18 = 13
-x = -5
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 3.
Solve the system of equations.%0D%0A–x+6y=13 %0D%0A4x–10y=–10 (1 point)%0D%0A(, )
1 answer